PELINDUNGAN HUKUM ATAS VAKSIN COVID-19 DAN TANGGUNG JAWAB NEGARA PEMENUHAN VAKSIN DALAM MEWUJUDKAN NEGARA KESEJAHTERAAN - Masnun, Muh. Ali; Sulistyowati, Eny; Ronaboyd, Irfa (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
Abstract The Covid-19 pandemic that has plagued various fields of life, both in the economic, political, education, until the Covid-19 pandemic outbreak was declared as national disaster. Based on that, various efforts are continuously being pursued for strategies to tackle the spread of the virus which has claimed a relatively large number of lives. Among other things, these efforts are through the policy of Large-Scale Social Restrictions, social distancing, including efforts to find the vaccine. The purpose of this study is to analyze the legal aspects of the Covid-19 vaccine and the responsibility of the State in fulfilling the Covid-19 vaccine. This research typology is a doctrinal research using primary and secondary legal materials using analytical descriptive. Based on the results of the analysis, it can be explained that the Covid-19 vaccine, besides having economic aspects, also has legal aspects that deserve attention. The economic aspect is that the Covid-19 vaccine is a necessity for everyone in the face of a pandemic, so that vaccines will become a sexy commodity that is definitely targeted and has high selling power. On the other hand, in supporting these commodities, it needs to be protected through a legal instrument known as protection of intellectual property rights, namely through a patent regime or trade secret. Choosing one of these has both advantages and disadvantages, so it needs to be considered carefully. The exclusivity of the Covid-19 vaccine in IPR is not something that can be exploited indefinitely, but the State can exist as a form of its responsibility through the application of compulsory licenses or disclosure of confidential information. Keywords: legal aspects; covid-19 vaccine dutch cemetry; responsibility of the stateAbstrakPandemi Covid-19 yang telah mewabah telah memberikan dampak berbagai bidang kehidupan, baik bidang ekonomi, politik, pendidikan, hingga kemudian wabah pandemi Covid-19 dinyatakan sebagai bencana nasional. Berdasarkan hal tersebut berbagai upaya terus diupayakan strategi untuk menanggulangi penyebaran virus yang telah menelan korban jiwa relatif banyak. Antara lain upaya tersebut melalui kebijakan Pembatasan Sosial Berskala Besar (PSBB), menjaga jarak (social distancing), termasuk upaya menemukan vaksinnya. Tujuan dari penelitian ini untuk menganalisis aspek hukum atas vaksin Covid-19 dan tanggung jawab Negara dalam pemenuhan vaksin Covid-19. Tipologi riset ini merupakan penelitian doktrinal dengan menggunakan bahan hukum primer maupun sekunder dengan menggunakan deskriptif analitis. Berdasarkan hasil analisis dapat dijelaskan bahwa vaksin Covid-19 di samping memiliki aspek ekonomi juga memiliki aspek hukum yang sangat patut diperhatikan. Aspek ekonomi bahwa vaksin Covid-19 sebagai kebutuhan semua orang dalam menghadapi pandemi, sehingga vaksin akan menjadi komoditi seksi yang sudah pasti diincar dan memiliki daya jual tinggi. Di sisi lain dalam menunjang komoditi tersebut perlu dilindungi melalui instrumen hukum yang dikenal dengan pelindungan hak kekayaan intelektual yakni melalui rezim paten atau pun rahasia dagang. Pemilihan salah satu tersebut masing-masing memiliki kelebihan maupun kelemahan, sehingga perlu dipertimbangkan secara matang. Eksklusivitas vaksin Covid-19 dalam HKI bukanlah sebuah hal yang dapat dieksploitasi tanpa batas, melainkan Negara dapat hadir sebagai bentuk tanggung jawabnya melalui penerapan lisensi wajib atau pengungkapan informasi yang bersifat rahasia.